Students' perception towards educational facilities in UiTM Pahang / Siti Aishah Mohamad, Ilyani Azer and Mohd Faizal Azrul Azwan Muhammed@Che Harun - Mohamad, Siti Aishah; Azer, Ilyani; Muhammed@Che Harun, Mohd Faizal Azrul Azwan (2012)
University should provide a range of educational facilities that enable excellent teaching and support student learning. Educational facilities including academic learning space, support space and exterior environment have impact on students' achievement (Me Gowen, 2007). As main customers to UiTM Pahang, students' perception towards the educational facilities should be taken into account. The institution of higher learning should fulfill their customer needs and wants. Therefore the aim of this study is to investigate the students' perception towards educational facilities since it will give an impact on their achievement, attendance, behavior and completion rate. Generally, the result found that most students agreed that the academic learning space, support space and exterior environment in UiTM Pahang fulfilled their educational needs. However this study also found that students made perception that parking space, cafeteria and maintenance of facility and vandalism are unsatisfactory. The finding from this study provides useful information to UiTM Pahang in making improvement on the facilities provided.